The Role of Zakat Institutions in Improving the Community's Economy - Sumadi Buton (Journal of Islamic Economy, 2025)
This study aims to analyze the role of zakat institutions in improving the community's economy through various empowerment programs. The research method used is a qualitative approach with a case study design. Data were collected through in-depth interviews with zakat institution managers, beneficiary mustahik, and community leaders, supplemented by documentation studies and field observations. The results show that zakat institutions contribute significantly to increasing the income and independence of mustahik through programs such as business capital assistance, skills training, and business mentoring. Some mustahik have even succeeded in improving their standard of living and becoming muzakki. However, zakat institutions still face challenges such as limited funds, low financial literacy among mustahik, and the need for innovation in empowerment programs. This study recommends the need to strengthen collaboration between zakat institutions and the government, the private sector, and academics to expand the socio-economic impact of zakat management.